2018
DOI: 10.3390/pharmacy6020039
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Community Pharmacy-Based Intervention to Optimize Patients’ Use of and Experience with Antidepressants: A Step-by-Step Demonstration of the Intervention Mapping Process

Abstract: Objective: To describe the development of a community pharmacy-based intervention aimed at optimizing experience and use of antidepressants (ADs) for patients with mood and anxiety disorders. Methods: Intervention Mapping (IM) was used for conducting needs assessment, formulating intervention objectives, selecting change methods and practical applications, designing the intervention, and planning intervention implementation. IM is based on a qualitative participatory approach and each step of the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Community pharmacists could reiterate that antidepressants should not be considered as a "quick fix", and ask monitoring questions throughout treatment, particularly as some men feel "lost in the system" when stabilised on the medication. In particular this study found a need for staggered support over time, and that is where the accessibility of community pharmacists could be particularly useful, a finding supported by other literature 79,80 . Some participants had unsuccessful attempts at stopping antidepressants and attributed this to placebo effects.…”
Section: Implications For Community Pharmacy Practicesupporting
confidence: 79%
“…Community pharmacists could reiterate that antidepressants should not be considered as a "quick fix", and ask monitoring questions throughout treatment, particularly as some men feel "lost in the system" when stabilised on the medication. In particular this study found a need for staggered support over time, and that is where the accessibility of community pharmacists could be particularly useful, a finding supported by other literature 79,80 . Some participants had unsuccessful attempts at stopping antidepressants and attributed this to placebo effects.…”
Section: Implications For Community Pharmacy Practicesupporting
confidence: 79%
“…The training programme developed specifically for IG pharmacists is outlined, following the six steps of the IM framework as outlined by Bartholomew et al (1998) and applied in other pharmacy settings (Labonté et al, 2020; Sabater-Hernández et al, 2016; Santina et al, 2018; Wheeler et al, 2018). This included: (1) needs assessment; (2) identification of programme objectives; (3) selection of theory-based methods and practical applications; (4) programme development; (5) adoption and implementation plan; and (6) evaluation plan.…”
Section: Resultsmentioning
confidence: 99%
“…Santina et al [ 2 ] used qualitative research as part of a mapping process to design a community-based pharmacy intervention. The authors conducted three descriptive exploratory qualitative studies that included different stakeholders and different data collection methods (individual interviews and focus groups).…”
mentioning
confidence: 99%
“…The authors conducted three descriptive exploratory qualitative studies that included different stakeholders and different data collection methods (individual interviews and focus groups). These data informed an Intervention Mapping (IM) process to design a community pharmacy-based intervention to optimise patients’ use of antidepressants [ 2 ]. This protocol outlined the steps involved in an IM process.…”
mentioning
confidence: 99%